Kidney Weight: The Pre-Clinical Analysis on the Influence of Probiotic Supplementation in Malnutrition - Rais Amaral Haq; Khairun Nisa Berawi; Chicy Widya Morfi; Nurul Islamy (Poltekkes Kemenkes Tanjung Karang, 2025)
A study showed malnutrition, encompassing both obesity and undernutrition, is a serious metabolic condition that leads to health complications, including kidney injury. Probiotics have been proposed as a potential adjuvant therapy to improve compensatory kidney function. However, research on the effects of probiotic intervention on kidney morphological changes across different nutritional statuses remains limited. This exploratory pilot study involved 24 male isogenic Sprague Dawley rats (n=24; 7-8 weeks old), which were divided into six groups (n=4): undernourished (KU), undernourished-probiotics (KU-P), normal (KN), normal-probiotics (KN-P), obese (KO), and obese-probiotics (KO-P). The rats underwent a 10-day dietary period, followed by a 44-day treatment period, and were terminated on day 45. The kidneys were then extracted and weighed using an analytical scale. Kidney weight data were analyzed using a non-parametric Kruskal-Wallis test, followed by post hoc Dwass-Steel-Critchlow-Fligner (DSCF) tests. Findings revealed a significant difference in kidney weight among the groups (p=0.001), with a substantial effect size. Descriptive trends showed that the obese (KO) group had the highest kidney weights, while the undernourished (KU) group had the lowest. The normal-probiotic group (KN-P) showed a trend toward increased kidney weight compared with the undernourished group (KU); however, conservative pairwise comparisons did not reach statistical significance (p>0.05) due to the limited sample size. Nutritional status is the primary factor influencing kidney weight. While probiotics demonstrated a corrective effect on kidney morphology in the normal group, their supplementation efficacy requires further evaluation, particularly in undernourished and obese conditions.